2013
DOI: 10.1051/0004-6361/201220482
|View full text |Cite
|
Sign up to set email alerts
|

Tidal damping of the mutual inclination in hierarchical systems

Abstract: Hierarchical two-planet systems, in which the inner body's semi-major axis is between 0.1 and 0.5 AU, usually present high eccentricity values, at least for one of the orbits. As a result of the formation process, one may expect that planetary systems with high eccentricities also have high mutual inclinations. However, here we show that tidal effects combined with gravitational interactions damp the initial mutual inclination to modest values in timescales that are shorter than the age of the system. This eff… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 48 publications
1
19
0
Order By: Relevance
“…As a simplified model, we only consider the dominating conservative terms of the secular hamiltonian (after averaging over the mean anomalies), namely the quadrupolar interaction with general relativity corrections (e.g., Correia et al 2013):…”
Section: Phase Portraitsmentioning
confidence: 99%
“…As a simplified model, we only consider the dominating conservative terms of the secular hamiltonian (after averaging over the mean anomalies), namely the quadrupolar interaction with general relativity corrections (e.g., Correia et al 2013):…”
Section: Phase Portraitsmentioning
confidence: 99%
“…we can use a quadrupolar approximation to study its secular dynamics (e.g. Kozai 1962;Correia et al 2013). As a result, the orbital evolution becomes integrable and easy to understand.…”
Section: Dynamical Evolutionmentioning
confidence: 99%
“…As a consequence, in the frame of a quadrupolar model the tidal evolution can be delayed to a maximum of 1.5 Gyr. However, this is not very realistic, because near the separatrix the inner orbit becomes chaotic, and the planet becomes a hot Jupiter in a few Myr (see Correia et al 2013).…”
Section: Dynamical Evolutionmentioning
confidence: 99%
“…The results showed that the inclusion of the R 4C term gives results that are worst than the ones given by the R 3C term, but the inclusion of the R 5C term corrects the problem. Correia et al (2013) shows that the effects of the tides combined with gravitational interactions helped to reduce the initial mutual inclination to small values on time scales. This effect is not a direct consequence of the tides on the orbits, but results from a secular forcing of the inner planet's flattening.…”
Section: Introductionmentioning
confidence: 98%
“…The choice of the small parameter (α) is made because, in general, the hierarchical systems have highly eccentric orbits which makes it difficult the expansion of the perturbation in series of the eccentricity. It is more convenient to use the ratio of the semi-major axis of the planet (a 1 ) and the disturbing star (a 2 ), because exact expressions can be computed for the secular system (see Correia et al 2013). The orbit of the disturbing star is considered to be elliptical, planar and fixed in space.…”
Section: Introductionmentioning
confidence: 99%